A Modern Course in Aeroelasticity:Fifth Revised and Enlarged Edition - Dowell, Earl (Springer, 2015)
his book cover the basics of aeroelasticity or the dynamics of fluid-structure interaction. While the field began in response to the rapid development of aviation, it has now expanded into many branches of engineering and scientific disciplines and treat physical phenomena from aerospace engineering, bioengineering, civil engineering, and mechanical engineering in addition to drawing the attention of mathematicians and physicists.